Genetic Architecture of Carcass and Meat Quality Traits in Montana Tropical® Composite Beef Cattle - Grigoletto, Laís; Ferraz, José B. S.; Oliveira, Hinayah R.; Eler, Joanir P.; Bussiman, Fernando O.; Abreu Silva, Barbara C.; Baldi, Fernando; Brito, Luiz F. (Frontiers in Genetics, 2020)
The Montana Tropical® Composite is a recently developed beef cattle population that is rapidly expanding in Brazil and other tropical countries. This is mainly due to its improved meat quality and adaptation to tropical climate conditions compared to Zebu and Taurine cattle breeds, respectively. This study aimed to investigate the genetic architecture of ultrasound-based carcass and meat quality traits in Montana Tropical® Composite beef cattle. Therefore, we estimated variance components, genetic parameters, and performed genome-wide association studies using the weighted single-step GBLUP approach. A pedigree dataset containing 28,480 animals were used, in which 1,436 were genotyped using a moderate-density Single Nucleotide Polymorphism panel (30K; 30,105 SNPs). A total of 9,358, 5,768, 7,996 and 1,972 phenotypic records for the traits Longissimus muscle area (LMA), backfat thickness (BFT), rump fat thickness (RFT) and for marbling score (MARB), respectively, were used for the analyses. Moderate to high heritability estimates were obtained and ranged from 0.16±0.03 (RFT) to 0.33±0.05 (MARB). A high genetic correlation was observed between BFT and RFT (0.97±0.02), suggesting that a similar set of genes affects both traits. The most relevant genomic regions associated with LMA, BFT, RFT, and MARB were found on BTA10 (5.4-5.8 Mb), BTA27 (25.2-25.5 Mb), BTA18 (60.6-61.0 Mb), and BTA21 (14.8-15.4 Mb). Two overlapping genomic regions were identified for RFT and MARB (BTA13:47.9-48.1 Mb), and for BFT and RFT (BTA13:61.5-62.3 Mb). Candidate genes identified in this study, including PLAG1, LYN, WWOX, and PLAGL2, were previously reported to be associated with growth, stature, skeletal muscle growth, fat thickness, and fatty acid composition. Our results indicate that ultrasound-based carcass and meat quality traits in the Montana Tropical® Composite beef cattle are heritable, and therefore, can be improved through selective breeding. In addition, various novel and already known genomic regions related to these traits were identified, which contribute to a better understanding of the underlying genetic background of LMA, BFT, RFT, and MARB in the Montana Tropical Composite population.